Motivasi Kerja Dan Peningkatan Jenjang Karier Terhadap Kompetensi Karyawan Mega Sejahtera - Latifah Jusdienar, Akka; Zulina Ayunani , Faras (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2025)
This article describes the independent variable. Workplace motivation andcareer advancement goals, along withemployee competency, can be summarized asfollows:Variable Work Motivation versus Competency Variable Within this context, thedecisive factor (KD) The tool or method used to adjust the dependent variable's meanvalue from the independent variable is usually regression analysis. Analyses ofregression allow researchers to understand relationships and how certain significantchanges in independent variables can affect dependent variables.In addition to it, thereare other methods such as:The Analysis of Variance, or ANOVA, is used to compare twoindependent variables to one dependent variable.Correlation analysis: this method is usedto estimate some strong correlation between two variables, yet it is not a completely silentway to identify causes. The following are some of the perhitungan techniques used: About is the value of thecoefficient of determination (r) 0.605.Using the determined rumus koefisien: KD isequal to r² × 100%. Measuring r²: \( r² = 0,605 × 0,605 = 0,366 \). Menghitung KD: \KDis equal to 0,366 × 100%, or 36,6%. Based on these results, it can be concluded that thework-related motivation variable affects the employee's skill level. This statementindicates the results of a regression analysis, or a method of analysis where 36,6% of thedependent variable is explained by the independent variable that was examined.Accordingly, the model's coefficient of determination (R2) is either 36,6% or 0,366. As anexample, 63.4% of the data indicate that dependent variables are affected byunidentified or unaccounted for factors in the research model.This could mean that there isanother variable anything should be considered in a more thorough study to increase the model's accuracy in explaining theaforementioned dependent variable.A slight deviation from the mean of 36.7% to 36.6%was observed based on the deviation of r².As a function of the Jenjang Karir Variable and the Karyawan Variable's Competency, the results are manually calculated using utilizing the following rumus koefisiendeterrninasi: KD = r2 x I 00%, where r is the result of a koefisien korelasi analysis with a significance level of 0.635. The results are as follows: KD is equal to r2 x 100%, 0,635 x100%, 0,403 x 100%, or 40,3%. It is possible to deduce from these findings that theJenjang Karir variable The statement above suggests that there is a significant relationshipbetween the variables Work Motivation and Karyawan Competency. The regressionanalysis's findings reveal a value of R of roughly 0.701, indicating a high degree ofcorrelation between the dependent variable (Karyawan Competency) and the independentvariables (Workplace Motivation and Employee Growth). In addition, the R Square (R²) value of 0.492, or 49.2%, indicates that 49.2% of theKaryawan competency variable can be explained by the two independent variablesmentioned above. exhibits a significant damping of 50.8%, which is the result of byunidentified supporting components in our study. In other words, both work motivationand Jenjang Karir training contribute positively and significantly to the development ofemployees' skills, and this relationship is quite strong.Key words: Motivation, Work, Hard work, Skill, and Ability